Vaccine hesitancy for childhood vaccinations in slum areas of Siliguri, India - Pallabi Dasgupta; Sharmistha Bhattacherjee; Abhijit Mukherjee; Samir Dasgupta (Wolters Kluwer Medknow Publications, 2018)
Background: Despite evidence regarding the beneficial effects of vaccines, vaccination uptake has not been up to the mark across the globe in various sociocultural and sociodemographic groups. Logistics and workforce have been issues of concern to public health managers, but the latent issue of vaccine hesitancy leading to vaccine delays and refusals has not been widely addressed particularly in the Indian context. Objectives: The present study was conducted to find out the proportion and factors contributing to vaccine hesitancy for childhood vaccinations in slums of Siliguri, India. Methods: A cross-sectional study was carried out among 194, 0-59 months' children residing in slums of Siliguri in 2016. Data were collected at the household with interviews of mothers/primary caregivers using a predesigned pretested interview schedule developed based on the validated version of vaccine hesitancy survey questionnaire originally developed by the World Health Organization Strategic Advisory Group of Experts working group on vaccine hesitancy. Associations were analyzed using logistic regression. Results: Majority 161 (83%) of the families were vaccine-hesitant and only 33 (17%) were not hesitant. Nuclear families and mothers of lower educational status had significantly higher odds of vaccine hesitancy. Reluctance to vaccinate (26.1%) and to be unaware/having no reliable information (20.5%) were the major reasons cited for vaccine hesitancy. Conclusion: Most of the families of the children were vaccine-hesitant in the area. Uniformity in schedules in different health facilities in slum areas, appropriate antenatal information, and counseling regarding childhood vaccinations, widespread awareness, and improving mothers' education can address the issue of vaccine hesitancy.